The role of cholesterol metabolism in tumor therapy, from bench to bed - Xia, Wenhao; Wang, Hao; Zhou, Xiaozhu; Wang, Yan; Xue, Lixiang; Cao, Baoshan; Song, Jiagui (Frontiers in Pharmacology, 2023)
Cholesterol and its metabolites have important biological functions. Cholesterol is able to maintain the physical properties of cell membrane, play an important role in cellular signaling, and cellular cholesterol levels reflect the dynamic balance between biosynthesis, uptake, efflux and esterification. Cholesterol metabolism participates in bile acid production and steroid hormone biosynthesis. Increasing evidence suggests a strict link between cholesterol homeostasis and tumors. Cholesterol metabolism in tumor cells is reprogrammed to differ significantly from normal cells, and disturbances of cholesterol balance also induce tumorigenesis and progression. Preclinical and clinical studies have shown that controlling cholesterol metabolism suppresses tumor growth, suggesting that targeting cholesterol metabolism may provide new possibilities for tumor therapy. In this review, we summarized the metabolic pathways of cholesterol in normal and tumor cells and reviewed the progression of novel tumor therapeutic strategy with the drugs targeting different stages of cholesterol metabolism from bench to bedside.